Unsettling the taken (for granted). (April 2020) - Howitt, Richard
Histories of colonial plunder produced geographies that settler societies take for granted as settled. While some aspects of the conqueror/settler imaginary have been unsettled in specific cases, and through the negotiation of new instruments such as the United Nations Declaration on the Rights of Indigenous Peoples, various national apologies and modern treaties, much unsettling remains to be done. New geographies of plunder, violence and abuse reinstate geographies of various kleptocracies across the planet, reinforcing the unnatural disasters of displacement, disfigurement and loss on many people, places and communities. This paper uses the framing offered by emergent discourses of Indigenous geographies to reconsider the task of unsettling the taken-for-granted privilege of settler dominance in Indigenous domains.